Bridge natural frequency estimation by extracting the common vibration component from the responses of two vehicles. (1st November 2017) - Nagayama, T.; Reksowardojo, A.P.; Su, D.; Mizutani, T.
Highlights: An indirect bridge frequency estimation strategy utilizing two vehicles is proposed. The estimation strategy improves the detectability of the bridge frequency. Sensitivity of the strategy with respect to vehicle's mass and stiffness variation is investigated. The estimation strategy is proved to be feasible through a field experiment. Abstract: Bridge natural frequencies are among fundamental properties of bridges. However, natural frequencies of most bridges remain unknown. Natural frequency identification through acceleration measurement with sensors installed on bridges is not practical if a large number of bridges are investigated. Indirect methods to detect the frequencies from the acceleration responses of a vehicle driving over bridges, on the other hand, still have difficulties. Vehicle responses contains various components, making it difficult to distinguish the bridge frequency from other frequency components. This study proposes new frequency estimation strategy utilizing two vehicles. The key idea is that bridge vibration, a common vibration component among responses of multiple vehicles, is extracted through signal processing involving cross-spectral density function estimation. Numerical analyses employing a vehicle-bridge interaction (VBI) model are conducted to examine the algorithm performance under various conditions. The numerical simulations have confirmed the feasibility of such indirect frequency detection. An experimental study featuring synchronized-sensing of two vehicles is then performed. The first natural frequency of the bridge has been identified under various driving speed combinations, demonstrating the performance of the proposed approach.